The impact of information and communication technology on the application of knowledge management -Case study of Optimum Telecom Algeria "Djezzy-" - fatima zohra aisaat; taha yacin merbah (Journal of Excellence for Economics and Management Research, 2021)
Our research paper, this study, seeks to identify the impact of information and communication technology on the application of knowledge management in Optimum Telecom Algeria "Djezzy". We used the Statistical Package for Social Sciences (SPSS) to analyze the questionnaire data. To achieve the objectives of the study, a questionnaire was designed and developed for the purpose of collecting data from the research sample members. A set of statistical methods were used to analyze the data statistically. The study concluded that there is a high level of information and communication technology and knowledge management. In Optimum Telecom Algeria "Djezzy", there is also a positive effect between these two variables, and the study recommends the need to create appropriate working conditions and enhance information and communication technology in order to enhance and ensure the success of modern administrative approaches.